Pendampingan Penggunaan Media Pemasaran Berbasis Digital Pada Umkm Hakim Mainan Edukasi - Sintya Oktarina; Dheny Indra Gunawan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Hakim Educational Toys is a home-based business located at Jalan Pedamaran Tamtin RT 02 RW 04 Kauman District, Semarang City. UMKM Hakim Educational Toys operates in the field of making children's educational toys. Marketing is still carried out using conventional methods, namely by selling through street vendors. This method makes the target market narrow because it only reaches the area around the production site. Conventional marketing is also felt to be less effective in improving the business development process. By designing the marketplace as a digital-based marketing medium, it is hoped that it can increase the turnover and productivity of Hakim Educational Toys MSMEs.